Aging away from home: a cultural context and workforce challenges for African Australians; the necessity for an ‘Afrocentric’ care model in Australia - Watts, Mimmie Claudine (Frontiers in Public Health, 2025)
This perspective examines the emerging African Australian older adult group, a minority group within a minority and the need for an Afrocentric-oriented workforce. It discusses aging and support systems within a traditional African setting, contrasted to the solitary state of the aging African Australian diaspora, while highlighting the presence of a CALD workforce ready to support their older adults. Intergenerational coresidency, a cultural practice common in African family structures, like Asian communities, are shared. The values of respect, communal existence, filial responsibilities, and the need for connections to kin by older adults are explored. The challenges facing older adult parents left behind in Africa, while their children search for better opportunities abroad, need addressing. Protracted issues of limited participation in the workforce earlier in life, and its subsequent impact on the individual’s later life, have profound financial impact on them. In conclusion, gaps in the workforce to meet the needs of an older adult minority group are sought. A proposed Afrocentric workforce framework to provide assistance to older adults is examined and proposed.